Stochastic dynamics construction of a three-dimensional microstructure of red clay - Zhang, Xiaohu; Zhang, Jiabing; Li, Xin; Ren, Xiao (Frontiers in Earth Science, 2023)
Constructing the microstructure of red clay is an important part of studying the physical and mechanical properties of red clay. The study of red clay microstructure is generalized. The red clay matrix and pores are regarded as two kinds of randomly moving particles respectively, and the microstructure model of three-dimensional red clay random porous media is established from the Langevin equation of the phase separation process in stochastic dynamics, using the separation and aggregation of the two particles. The model controls the evolution process of the porous medium by artificially controlling the particle placement. The trends of porosity, averaged pore length, Euler number and fractal dimension of the porous medium during the evolution process under different parameter conditions (smooth length Δ and rise and fall term η) are calculated, and a feasible method for surviving the microstructure of red clay is summarized. Due to the consideration of the interaction forces between the solid and void phase particles, the porous media generated by this model are closer to the real porous media in nature, with connected and unconnected pore structures and tortuous pore channels. Finally, the red clay of Bijie, Guizhou, is modeled as an example to prove the feasibility of the method.